AKTUALISASI STATUS SOSIAL MELALUI UPACARA ADAT MASYARAKAT BATAK TOBA DI KAWASAN DANAU TOBA - Harisan Boni Firmando (Department of Anthropology, 2022)
This paper aims to see the extent to which the provision of food and drink in the traditional ceremonies of the Batak Toba people is a means of actualizing social status. This study uses qualitative methods with data collection techniques of observation, interviews, document studies and focus group discussions (FGD). The results show that there is a relationship between culture and social status, where traditional ceremonies are the arena for the Toba Batak community to actualize social status. Actualization of social status is carried out through efforts to give gifts in the form of giving and receiving food and drinks in various traditional ceremonies among relatives. In principle, the provision of food and drink is only given in a perfunctory manner, in accordance with the rules or habits that have been carried out by the ancestors or previous parents, but now there has been a change. Ironically, the change is not because of important situations and needs, but because of self-actualization efforts to show family identity or someone who is in a high social class.Abstrak: Tulisan ini bertujuan untuk melihat sejauh mana pemberian makanan dan minuman dalam upacara adat masyarakat Batak Toba menjadi sarana aktualisasi status sosial. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data observasi, wawancara, studi dokumen dan focus group discussion (FGD). Hasil penelitian menunjukkan bahwa terdapat relasi antara budaya dan status sosial, dimana upacara adat menjadi arena masyarakat Batak Toba untuk mengaktualisasikan status sosial. Aktualisasi status sosial dilakukan melalui usaha-usaha memberikan hadiah yang berupa pemberian dan penerimaan makanan dan minuman dalam berbagai upacara adat di antara unsur kerabat. Pemberian makanan dan minuman pada prinsipnya hanya diberikan ala kadarnya, sesuai dengan aturan atau kebiasaan yang telah dijalankan oleh leluhur atau orang tua terdahulu, namun kini telah terjadi perubahan. Ironisnya perubahan tersebut bukan karena situasi dan kebutuhan yang penting, namun karena adanya upaya mengaktualisasikan diri untuk menunjukkan identitas keluarga atau seseorang yang berada pada kelas sosial yang tinggi.